2017
DOI: 10.1038/nchem.2779
|View full text |Cite
|
Sign up to set email alerts
|

Cytosolic antibody delivery by lipid-sensitive endosomolytic peptide

Abstract: One of the major obstacles in intracellular targeting using antibodies is their limited release from endosomes into the cytosol. Here we report an approach to deliver proteins, which include antibodies, into cells by using endosomolytic peptides derived from the cationic and membrane-lytic spider venom peptide M-lycotoxin. The delivery peptides were developed by introducing one or two glutamic acid residues into the hydrophobic face. One peptide with the substitution of leucine by glutamic acid (L17E) was show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

13
352
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 298 publications
(382 citation statements)
references
References 47 publications
13
352
1
Order By: Relevance
“…[38] To verify that 3 can be successfully delivered into the cytosol, we co-incubated DU145 and HeLa cells with 6 mm of 3.Although we observed acceptable delivery (see Figure S6), the addition of endosomolytic L17E peptide [12] further improved its delivery ( Figures 3A,D). [38] To verify that 3 can be successfully delivered into the cytosol, we co-incubated DU145 and HeLa cells with 6 mm of 3.Although we observed acceptable delivery (see Figure S6), the addition of endosomolytic L17E peptide [12] further improved its delivery ( Figures 3A,D).…”
Section: Resultsmentioning
confidence: 89%
See 1 more Smart Citation
“…[38] To verify that 3 can be successfully delivered into the cytosol, we co-incubated DU145 and HeLa cells with 6 mm of 3.Although we observed acceptable delivery (see Figure S6), the addition of endosomolytic L17E peptide [12] further improved its delivery ( Figures 3A,D). [38] To verify that 3 can be successfully delivered into the cytosol, we co-incubated DU145 and HeLa cells with 6 mm of 3.Although we observed acceptable delivery (see Figure S6), the addition of endosomolytic L17E peptide [12] further improved its delivery ( Figures 3A,D).…”
Section: Resultsmentioning
confidence: 89%
“…Recent examples of delivery methods of proteins include the use of endosomolytic peptides, [12,13] poly(disulfide)s, [14] microinjection, [15] electroporation, [16] small-molecule additives, [17] bioreversible esterification, [18] and modifying the target protein with cell-penetrating peptides (CPPs). Recent examples of delivery methods of proteins include the use of endosomolytic peptides, [12,13] poly(disulfide)s, [14] microinjection, [15] electroporation, [16] small-molecule additives, [17] bioreversible esterification, [18] and modifying the target protein with cell-penetrating peptides (CPPs).…”
Section: Introductionmentioning
confidence: 99%
“…[2,4] Therefore, intracellular delivery of functional, native proteins (including antibodies) remains akey challenge in protein-based therapy. [10] Although the delivered cargos were unmodified, their slow endosome escape was not ideal for immediate bioavailability.The noncovalent L17E/cargo formulation also limits the type of proteins that could be used and delivery efficiency.O ff ew reports that showed successful delivery of proteins directly into the cytoplasm of mammalian cells,all of them require genetic and/or chemical modifications to the cargos, [11][12][13] and almost none allows intracellular release of "native" proteins to enable full restoration of their activities. Futaki et al reported an endosomolytic peptide (i.e., L17E) that forms noncovalent complexes with various proteins,l eading to cell entry via endocytosisfollowed by successful cytosolic protein liberation.…”
mentioning
confidence: 99%
“…To overcome this issue, numerous strategies, such as introduction of the endosomolytic agents used to disrupt endosomal membrane, have been developed to improve the stability and transporting efficiency. [229] Recently, a cationic, amphiphilic peptide with a strong membrane lytic activity was selected as template for the endosomolytic peptides by Akishiba et al [230] This endosomolytic peptides (L17E) were developed by introducing one or two negatively charged glutamic acid residues into the hydrophobic face. [227] Nischan and co-workers synthesized another cyclic CPP to promote the GFP delivery in the cytosol and nucleus.…”
Section: Cell-penetrating Peptidesmentioning
confidence: 99%
“…In addition, peptides have the advantage of being nonimmunogenic in comparison to the antibodies. [230] Copyright 2017, Springer Nature. [231] However, some limitations, Adv.…”
Section: Cell-penetrating Peptidesmentioning
confidence: 99%